Gold-catalyzed C(sp2)-C(sp) coupling by alkynylation through oxidative addition of bromoalkynes - Yang, Yangyang; Schießl, Jasmin; Göker, Verena; Gross, Jürgen H.; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2019)
A gold(I)-catalyzed cascade cyclization-alkynylation of allenoates using alkynyl bromide to generate β-alkynyl-γ-butenolides was investigated. Whereas alkynyl iodides afforded significant amounts of the homo-coupling of two lactone units, alkynyl bromides led to a selective reaction, and a broad functional group tolerance was observed. Under the optimized reaction conditions, it was possible to directly synthesize a large range of β-alkynyl-γ-butenolides in moderate to good yields without the need for any external oxidant.